2016
DOI: 10.1016/j.jshs.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of karate and fitness training on cognitive functioning in older adults—A randomized controlled trial

Abstract: BackgroundRecent studies demonstrate a slowdown in deterioration of cognitive functioning in old age through aerobic training. There is evidence that the combination of aerobic, balance, and coordination exercises leads to an improvement or maintenance of cognitive functions. Such age-related exercises can especially be found in East Asian martial arts. The purpose of the current study is to verify whether karate training for older adults improves cognitive functioning and, if an improvement can be found, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
6

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 22 publications
(31 reference statements)
0
59
0
6
Order By: Relevance
“…A brief look at some of these shows a range of benefits. For example, in a randomised control trial (RCT) of 200 adults with a mean age of 70, results showed that karate improved attention, resilience and motor reaction time for the participants in the research (Witte and Böckelmann, 2016). In another study, 456 participants over the age of 60 who had visited an emergency room in a hospital, as the result of a fall within a six-month period, took part in an RCT in Taiwan.…”
Section: Eastern Philosophy and Its Relevance To Martial Artsmentioning
confidence: 99%
“…A brief look at some of these shows a range of benefits. For example, in a randomised control trial (RCT) of 200 adults with a mean age of 70, results showed that karate improved attention, resilience and motor reaction time for the participants in the research (Witte and Böckelmann, 2016). In another study, 456 participants over the age of 60 who had visited an emergency room in a hospital, as the result of a fall within a six-month period, took part in an RCT in Taiwan.…”
Section: Eastern Philosophy and Its Relevance To Martial Artsmentioning
confidence: 99%
“…Oriental gymnastics and martial arts are considered physical and cognitive activities performed simultaneously, through standardized movements that have a higher level of complexity in relation to the repetitive movements of aerobic or resistance exercises (9)(10)(11) . Thus, studies from the practice of Yoga (12)(13) and Tai Chi Chuan (14) , among others, demonstrate that these activities can provide considerable cognitive gains (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Dessa maneira, modalidades como o Karatê e a Ginástica Generalizada, que abrangem diversificadas respostas comportamentais diante de situações de equilíbrio estático e dinâmico, caracterizadas por perturbar constantemente o sistema de controle postural, ainda são pouco exploradas. Alguns autores [21][22][23][24] discutem o efeito positivo do treinamento do Karatê, como prática de habilidades motoras que podem influenciar de maneira positiva, em respostas de ações motoras mais rápidas para o controle postural. Benefícios são a melhoria na aptidão, agilidade, concentração, autocontrole e mobilização, além de evidências de melhoras das funções cognitivas 22,24 .…”
Section: Introductionunclassified
“…Alguns autores [21][22][23][24] discutem o efeito positivo do treinamento do Karatê, como prática de habilidades motoras que podem influenciar de maneira positiva, em respostas de ações motoras mais rápidas para o controle postural. Benefícios são a melhoria na aptidão, agilidade, concentração, autocontrole e mobilização, além de evidências de melhoras das funções cognitivas 22,24 . A ginástica generalizada é uma modalidade mais comum aos idosos, com exercícios que envolvam a coordenação motora, agilidade, equilíbrio, fortalecimento de membros inferiores e superiores 24 .…”
Section: Introductionunclassified
See 1 more Smart Citation